Compendium of standards for indigent defense systems: Resource guide for practitioners and policymakers - (:unkn) unknown (My University, 2016)
The Compendium of Standards for Indigent Defense Systems brings together standards from a wide variety of sources and shows the different ways in which they addresspractice and procedure: administration of defense systems, attorney performance, capital case representation, appellate services, and juvenile justice defense. Included are standards and rules issued by national organizations; by state agencies and special interest groups, including bar associations, public defender organizations, and state high courts; and by local court systems.